Coastal defence - Brampton, Alan (ICE design and practice guide., 2002)
Planning, designing, building and managing coastal defences in a cost-effective, environmentally acceptable and sustainable manner is a complicated undertaking. Coastal Defence offers an introductory handbook to this challenging subject matter.